Influence of macrophyte integrity on zooplankton habitat preference, emphasizing the released phenolic compounds and chromophoric dissolved organic matter - Gutierrez, Marìa Florencia (2016)
Macrophyte health status can influence the composition of their exudates causing different effects on zooplankton behavior and distribution in nature. We hypothesize that: (1) the release of phenolic compounds and chromophoric dissolved organic matter (CDOM) depends on macrophyte species and its health status (broken macrophytes: BM, or healthy macrophytes: HM); (2) the repellency effect depends on zooplankton species, macrophyte species and its health status; and (3) higher concentrations of phenolic compounds and CDOM produce a stronger repellency effect. Phenolic compounds and CDOM were analyzed in exudates of BM and HM of Salvinia sp., Eichhornia crassipes, Pistia stratiotes, Azolla sp. and Ludwigia peploides. Through a flow-through experiment, the repellency produced by these exudates was assessed in two copepods (Notodiaptomus conifer and Argyrodiaptomus falcifer) and one cladoceran (Ceriodaphnia dubia). Our hypotheses were partially validated. The quantity of exudated phenolic compounds and CDOM depended on macrophyte species and, to a lesser extent, on the plant health status. The repellency effect was affected by macrophyte and zooplankton species but not by the health status of plants. Only C. dubia and A. falcifer increased their evasion behavior when phenolic compound and CDOM concentrations increased. In brief, the structuring effect of repellent substances depends on different factors. Under a certain threshold concentration, zooplankton behavior might depend on the information associated with the plant odor (e.g., predation risk, structural complexity) more than on the quantity of the released chemical compounds. Above this threshold, evasion would be the only possible option to avoid damaging effects.